التنمية و الحكم الصالح - وصال علي محمد م.د. (lark, 2020)
The relation between development and good governance is expanded to include the researchers the interests of the researchers in the field of sociology studies in general and socio -politics especially because it is complex relation and does not include the simple meaning of the political system but it exceeds the society performance for all formal and informal institutions in the society as well as the variables that exceeds the individual income such as health , education age average and social welfare . Iraqi society needs a government system where the people become citizens gathered by the spirit of cooperation and common solidarity to achieve social structure . The study objectives includes learning the specified concepts such as development , poverty ,marginalizing, participation , social class and the kind of relation between them and the good governance and know the important strategic matters in development process to serve the good governance , reconstruct it and to reach the learning of how to reconstruct Iraq after wars and armed violence and why the development is an important in reconstruction . The researcher reached to the following conclusions • The good governance enforce and support human welfare as it expand the human abilities and chooses on economic, political and social levels The good governance makes elected political leadership and administrative staff that are committed to develop the society resources , serve the people and improve their standard of life , living and welfare as well as all the people are equal under the slogan of development and good governance .The political system should not be successful only in development in increase the income and local production but also in the light of the new standard of development ,treatment of illiteracy problem , increase education ,interest in women affairs and remove violence from women